Identification of new anti-inflammatory agents based on nitrosporeusine natural products of marine origin - Philkhana, Satish Chandra; Verma, Abhishek Kumar; Jachak, Gorakhnath R.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2017)
Nitrosporeusines A and B are two recently isolated marine natural products with novel skeleton and exceptional biological profile. Interesting antiviral activity of nitrosporeusines and promising potential in curing various diseases, evident from positive data from various animal models, led us to investigate their anti-inflammatory potential. Accordingly, we planned and synthesized nitrosporeusines A and B in racemic as well as enantiopure forms. The natural product synthesis was followed by preparation of several analogues, and all the synthesized compounds were evaluated for in vitro and in vivo anti-inflammatory potential. Among them, compounds 25, 29 and 40 significantly reduced levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines. In addition, these compounds suppressed several pro-inflammatory mediators including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF -kappa B), and thereby can be emerged as potent anti-inflammatory compounds. Furthermore, all possible isomers of lead compound 25 were synthesized, characterized and profiled in same set of assays and found that one of the enantiomer (-)-25a was superior among them. (C) 2017 Elsevier Masson SAS. All rights reserved.

Nitrosporeusine analogue ameliorates Chandipura virus induced inflammatory response in CNS via NF kappa b inactivation in microglia - Verma, Abhishek Kumar; Waghmare, Trushnal S.; Jachak, Gorakhnath R.; Philkhana, Satish Chandra; Reddy, D. Srinivasa; Basu, Anirban (PLOS Neglected Tropical Diseases, 2018)
Chandipura Virus (CHPV), a negative-stranded RNA virus belonging to the Rhabdoviridae family, has been previously reported to bring neuronal apoptosis by activating several factors leading to neurodegeneration. Following virus infection of the central nervous system, microglia, the ontogenetic and functional equivalents of macrophages in somatic tissues gets activated and starts secreting chemokines, thereby recruiting peripheral leukocytes into the brain parenchyma. In the present study, we have systemically examined the effect of CHPV on microglia and the activation of cellular signalling pathways leading to chemokine expression upon CHPV infection. Protein and mRNA expression profiles of chemokine genes revealed that CHPV infection strongly induces the expression of CXC chemokine ligand 10 (CXCL10) and CC chemokine ligand 5 (CCL5) in microglia. CHPV infection triggered the activation of signalling pathways mediated by mitogen-activated protein kinases, including p38, JNK 1 and 2, and nuclear factor kappa B (NF-kappaB). CHPV-induced expression of CXCL10 and CCL5 was achieved by the activation of p38 and NF-kappaB pathways. Considering the important role of inflammation in neurodegeneration, we have targeted NF-kappaB using a newly synthesised natural product nitrosporeusine analogue and showed incapability of microglial supernatant of inducing apoptosis in neurons after treatment.

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A